CAD/CAM implant crowns in a digital workflow: Five‐year follow‐up of a prospective clinical trial. (26th October 2018) - Joda, Tim; Bragger, Urs; Zitzmann, Nicola U.
Abstract: Background: Implant restorations became the first choice for single‐tooth replacement today. Purpose: The prospective clinical trial aims to investigate computer‐aided‐design (CAD)/computer‐aided‐manufacturing (CAM)‐processed implant crowns after 5 years of loading. Materials and Methods: Twenty patients were included for cement‐retained crowns in posterior sites. Radiographic analysis of bone levels was performed after delivery and follow‐up. The Functional Implant Prosthodontic Score (FIPS) was assessed at the final follow‐up. Wilcoxon signed‐rank tests were used with a level of significance set at α = 0.05. Results: One implant was lost, resulting in a success rate of 95% at 5 years. For 19 crowns, neither technical complications nor biological complications were observed. The mean marginal bone level was 0.6 ± 0.26 mm (range: 0.18‐1.12) mesially, and 0.79 ± 0.36 mm (range: 0.23‐1.36) distally at 5 years. During the observation period, mean radiographic bone levels increased significantly by 0.23 mm at mesial and by 0.17 mm at distal sites ( P  < .0001) indicating minor additional bone loss. The mean total FIPS score was 8.2 ± 1.0 (range: 7‐10) with the high score of 2.0 ± 0.0 for the variable "bone." Conclusions: CAD/CAM‐processed implant crowns demonstrated promising radiographic and clinical outcomes after 5 years in function. Future large‐scale trials are crucial to confirm these initial results in the field of digital implant processing.